7 - Exploring COVID-19 Lockdowns in Nigeria, South Africa and Botswana: Issues, Contexts and Controversies - Sebeelo, Tebogo (Africa Development, 2024)
The coronavirus-19 (Covid-19) pandemic has impacted the world in unprecedented ways. To contain the virus, countries across the world had to implement lockdowns and other Covid-19-related protocols, which included physical distancing, frequent handwashing, wearing masks and restricting the movement of people. Although literature on the impact of Covid-19 is emerging, it is still relatively unknown how countries in sub-Saharan Africa (SSA) dealt with lockdowns. Applying nudge theory to three case studies— Nigeria, South Africa and Botswana—this paper explores the viability of Covid-19 lockdowns in SSA. The three cases shed light on the dynamics of Covid-19 lockdowns across different contexts in SSA. The paper argues that lockdowns were not ideal for regions like SSA, which has one of the world’s poorest populations. Nudging people’s behaviour in an effort to protect them from harm should, we submit, consider their socioeconomic context. More importantly, there is a need to decolonise, adapt and domesticate Western- style interventions like Covid-19 lockdowns to suit different situations. To this end, the paper provides some critical insights into the experience of lockdowns with some policy implications for future pandemics on the African continent and other parts of the global South.